Waste Management Based on Maqashid Shari'ah And Circular Economy: Evidence in Blitar Regency - Aryanti Nur Azizah; Ahmad Djalaluddin; Siswanto Siswanto (Maliki Islamic Economics Journal, 2021)
The study of waste management based on maqashid shari'ah and circular economy requires a study to realize wise and Islamic waste management. This research comes with the aim to find out and analyze waste management based on maqashid shari'ah and circular economy in TPST 3R Blitar Regency, namely TPST 3R "Abdi Karya mandiri" and TPST 3R "Punokawan".  This research uses a qualitative approach with this type of case study research because this study examines an event that occurs today, which is related to waste management based on maqashid shari'ah and circular economy. Data excavation methods use observation, interview and documentation methods. In this study it was found that maqashid shari'ah-based waste management in TPST 3R Blitar Regency indirectly meets the five main elements of shari'ah maqashid, namely hifzh al-din, hifzh al-nafs, hifz al 'aql, hifzh hifzh al-nasl, and hifzh al-mal. Then in circular economy-based waste management at TPST 3R Blitar Regency produces sustainable and renewable products that are indirectly in accordance with the circular economy concept. This is because the waste management and processing system in the two TPST 3R has a rotating and interconnected production flow from upstream to downstream.